Analysis of Differences in Consumer Perceptions of Service Quality from an Islamic Perspective (Study of Panorama Traditional Markets and Hypermart Modern Markets) - Nana Aprina; Desi Isnaini; Faisal Muttaqin (Yayasan Darussalam Bengkulu, 2024)
The purpose of this research is to determine the differences in consumer perceptions of service quality, namely: the direct evidence dimension (tangibles), the reliability dimension, the responsiveness dimension, the assurance dimension, and the empathy dimension in the traditional market